Preparation method of monatomic synergistic coordination composite photoelectric catalyst

By combining Bi2S3-SV with Co-N4-C and using formaldehyde or dye to replace traditional hole sacrificial agents, the problem of adding sacrificial agents is solved in the process of photocatalytic or photoelectro-catalytic water cracking and hydrogen production, and the effect of high-efficiency photoelectro-catalytic hydrogen production coupled formaldehyde oxidation is achieved.

CN119800433AActive Publication Date: 2025-04-11NANCHANG HANGKONG UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510286556.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-11
Estimated Expiration
2045-03-12

AI Technical Summary

Technical Problem

The addition of sacrificial agents is required during the hydrogen production process of photocatalytic or photoelectric catalytic water cracking, resulting in an increase in carbon emissions and an increase in cost. At the same time, photogenerating electrons and holes are easy to recombinate, and there are few reactive sites.

Method used

The non-metal defect (sulfur/oxygen vacancies) and amorphous substrates are used to coordinate the variable valence single atoms, in situ growth strategies and solvent heat, and other methods are used to recombine the defect-rich Bi2S3-SV with Co-N4-C, introduce sulfur defects through liquid phase sulfurization, and promote the migration of Co single atoms to the Bi2S3-SV interface through annealing process to form a Co-Sy and Co-N4 coordination structure, and use formaldehyde or dye to replace traditional hole sacrificial agents.

Benefits of technology

It significantly improves the light absorption range and ability of the catalyst, improves the separation and migration ability of photogenerated electrons and holes, enhances the adsorption and activation ability of formaldehyde, reduces the recombination of photogenerated electrons and holes, promotes the adsorption and dissociation of H2O molecules, provides the required H+ for photoelectro-catalyzed hydrogen production reaction, and realizes high-efficiency photoelectro-catalyzed hydrogen production and coupled formaldehyde oxidation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800433A_ABST
    Figure CN119800433A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a monatomic synergistic coordination composite photoelectric catalyst, which utilizes nonmetal defects (sulfur / oxygen vacancies) and an amorphous substrate to synergistically anchor variable valence monatomic, an in-situ growth strategy, solvothermal methods and the like to realize coordination compounding of Bi2S3-SV and Co-N4-C, and uses thioacetamide as a sulfur source through a liquid-phase vulcanization method, bi2S3-SV is generated in situ, sulfur defects are directly introduced in the sulfuration process by regulating and controlling the proportion of a sulfur source and reducing the concentration of thioacetamide, then Co monatomic is promoted to migrate to a Bi2S3-SV interface in combination with an annealing process, Co-Sy coordination is formed, Co-N4 coordination in an N-C framework is reserved, and the Bi2S3-SV is prepared. The invention constructs a unique Bi2S3-SV / Co-N4-C composite photoelectric catalyst which realizes efficient photoelectrocatalytic hydrogen production coupled formaldehyde oxidation and other reactions through a unique sulfur vacancy and Co monatomic double coordination synergistic effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoelectric catalysts, and in particular to a method for preparing a single-atom cooperative coordination composite photoelectric catalyst. Background Art

[0002] In the process of photocatalytic or photoelectrocatalytic water splitting to produce hydrogen, the addition of sacrificial agents not only increases carbon emissions, but also increases the cost of the reaction process. One of the important research directions in the field of catalysis is to construct a catalyst that can achieve photocatalytic or photoelectrocatalytic water splitting to produce hydrogen in a sacrificial agent-free environment, even in electrolyte solutions containing pollutants, and at the same time couple the anodic oxidation reaction. Summary of the invention

[0003] The present invention provides a method for preparing a single-atom cooperative coordination composite photoelectric catalyst, which is used to solve the problems of needing to add a sacrificial agent, easy recombination of photogenerated electrons and holes, and lack of reaction active sites in the process of photocatalysis or photoelectrocatalytic material water splitting to produce hydrogen.

[0004] The present invention adopts the following technical solution:

[0005] A method for preparing a single-atom cooperative coordination composite photoelectrocatalyst, using non-metallic defects (sulfur / oxygen vacancies) and amorphous substrates to coordinately anchor variable-valence single atoms and in-situ growth strategies and solvothermal methods to achieve Bi2S3-S V The coordination complex of Co-N4-C and Bi2S3-S was generated in situ by liquid phase sulfurization with thioacetamide as the sulfur source. V By adjusting the sulfur source ratio and reducing the concentration of thioacetamide, sulfur defects were directly introduced during the sulfurization process, and then the annealing process was combined to promote the transfer of Co single atoms to Bi2S3-S V Interface migration to form Co-S y In addition, formaldehyde and dyes were used to replace traditional hole sacrificial agents to consume a large number of holes, and a unique sulfur vacancy and Co single atom double coordination synergistic effect was constructed to achieve efficient photoelectrocatalytic hydrogen production coupled with formaldehyde oxidation and other reactions. V / Co-N4-C catalytic system. The preparation method steps are as follows:

[0006] (1) Take a certain amount of Co(NO3)2·6H2O and 2-MI and dissolve them in an appropriate amount of methanol solution. After stirring for 5-120 min, let it stand for 1-12 h, and collect it by centrifugation to obtain ZIF-67 crystals.

[0007] (2) placing a certain amount of ZIF-67 crystals obtained in step (1) in a N2 atmosphere, heating to a certain temperature and maintaining it for 1-6 h, and then cooling to room temperature in the furnace to obtain Co-N4-C;

[0008] (3) Take a certain amount of Bi(NO3)3·5H2O and dissolve it in an appropriate amount of ethanol solution. After stirring until it is completely dissolved, add a certain amount of Co-N4-C and disperse it in it. After ultrasonic immersion for 10-180 min, dry it to obtain Co-N4-C@Bi 3+ ;

[0009] (4) Take a certain amount of Co-N4-C@Bi 3+ and a certain amount of TAA are dissolved in an appropriate amount of deionized water / ethylene glycol mixed solution and stirred thoroughly for 10-120 min;

[0010] (5) The solution stirred completely in step (4) was transferred into a solvent thermal reactor and reacted at a certain temperature for 6-24 h. The obtained product was washed and vacuum dried to obtain Co-N4-C@Bi2S3-S V ;

[0011] (6) A certain amount of Co-N4-C@Bi2S3-S V Place it in an Ar atmosphere, heat it to a certain temperature and keep it for 30-240 minutes, and then cool it to room temperature to obtain Bi2S3-S V / Co-N4-C composite photoelectrocatalyst.

[0012] Preferably, the mass of Co(NO3)2·6H2O used in step (1) is 0.1-10 g, the mass of 2-MI is 0.1-10 g, and the volume of the methanol solution is 10-1000 mL.

[0013] Preferably, the mass of ZIF-67 used in step (2) is 0.1-20 g, and the heating temperature is 600-1000 °C.

[0014] Preferably, in step (3), the mass of Bi(NO3)3·5H2O is 0.1-10 g, the volume of the ethanol solution is 10-1000 mL, the mass of Co-N4-C is 0.1-10 g, the drying temperature is 40-90 °C, and the drying time is 6-24 h.

[0015] Preferably, the Co-N4-C@Bi used in step (4) 3+ The mass of is 0.1-20 g, the mass of TAA is 0.1-20 g, the volume fraction of the deionized water / ethylene glycol mixed solution is 5-95%, and the volume of the deionized water / ethylene glycol mixed solution is 10-1000 mL.

[0016] Preferably, in step (5), the reaction temperature of the solvent thermal reactor is 120-350°C, the vacuum drying temperature is 40-90°C, and the time is 6-24 h.

[0017] Preferably, the Co-N4-C@Bi2S3-S V The mass is 0.1-20 g and the heating temperature is 200-600 ℃.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] The defect-rich Bi2S3-S was synthesized by synergistically anchoring variable-valence single atoms on non-metallic defects (sulfur / oxygen vacancies) and amorphous substrates, and by in-situ growth strategies and solvothermal methods. V The preparation process is simple and the production cost is low. Formaldehyde or dye solution is used to replace the traditional hole sacrificial agent to consume a large number of holes, and a unique sulfur vacancy and Co single atom double coordination synergistic effect is constructed to achieve efficient photoelectrocatalytic hydrogen production coupled with formaldehyde oxidation and other reactions. V The results show that the Co-N4 site can stabilize the Co atom and regulate its d-band center, thus enhancing the adsorption and activation of formaldehyde, and the generated S vacancy defect can form a composite coordination structure of Co-N / S with the amorphous substrate (Co-N4-C), which confirms that the local electric field polarization induced by sulfur vacancies can be used to adsorb single atom precursors (Co 2+ ), and realize dynamic coordination through the short-range ordered interface of the amorphous substrate, inhibit the migration and aggregation of Co single atoms, accelerate the transfer of holes to molecules such as formaldehyde, and cooperate with sulfur vacancies as electron capture centers to reduce the recombination of photogenerated electrons and holes, and promote the adsorption and dissociation of H2O molecules (H2O → H + + OH - ), providing the required H for the photoelectrocatalytic hydrogen production reaction (HER) + In addition, sulfur vacancies can also optimize the electronic structure of the Bi2S3 surface and reduce the activation energy of formaldehyde oxidation to achieve Bi2S3-S V / Co-N4-C highly efficient photoelectrocatalytic hydrogen production coupled with anodic oxidation of formaldehyde, etc., and is expected to be applied in the fields of photocatalytic or photoelectrocatalytic reduction of CO2, degradation of pollutants and production capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a flow chart of sample preparation in a method for preparing a single-atom cooperative coordination composite photoelectric catalyst of the present invention.

[0021] Figure 2 The Bi2S3-S prepared in the preparation method of the single-atom cooperative coordination composite photoelectric catalyst of the present invention V Spherical aberration electron microscope images of / Co-N4-C composite material at different scales.

[0022] Figure 3 The Bi2S3-S prepared in the preparation method of the single-atom cooperative coordination composite photoelectric catalyst of the present invention V Synchrotron radiation spectrum of / Co-N4-C composite material.

[0023] Figure 4 This is a photoelectrocatalytic performance diagram of a sample prepared in an example of a method for preparing a single-atom cooperative coordination composite photoelectrocatalyst of the present invention. DETAILED DESCRIPTION

[0024] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0025] In the process of photocatalytic or photoelectrocatalytic water splitting to produce hydrogen, the addition of sacrificial agents not only increases carbon emissions, but also increases the cost of the reaction process. One of the important research directions in the field of catalysis is to construct a catalyst that can achieve photocatalytic or photoelectrocatalytic water splitting to produce hydrogen in a sacrificial agent-free environment, even in electrolyte solutions containing pollutants, and at the same time couple the anodic oxidation reaction.

[0026] The increase in the hydrogen evolution rate in the electrolyte solution containing pollutants indicates that the pollutants act as hole sacrificial agents, consuming a large number of holes, thereby promoting the transport of carriers and ultimately improving the hydrogen evolution performance.

[0027] In the Co-N4-C obtained by carbonization of ZIF-67, Co single atoms are anchored in the amorphous NC support in the form of Co-N4 coordination, forming atomically dispersed active centers, and the NC support can effectively prevent the aggregation of Co single atoms. This coordination structure stabilizes Co atoms through the bonding of nitrogen atoms to the carbon matrix, while giving it a unique electronic structure, enhancing the adsorption and activation ability of formaldehyde or other reaction intermediates. In addition, during the catalytic reaction, Co 2+ / Co 3+ The cycle can dynamically regulate the local electron density, promote the formation of OOH or H intermediates, and reduce the reaction energy barrier.

[0028] Sulfur vacancies introduce defect states in Bi2S3, extending the light response range to the visible light and even the near-infrared region. At the same time, sulfur vacancies act as electron capture centers, greatly reducing the recombination rate of photogenerated carriers and the activation energy of formaldehyde oxidation, and effectively inhibiting the photocorrosion of Bi2S3. In addition, the Bi sites exposed by sulfur vacancies are more sensitive to H2O or OH - It has strong adsorption capacity and provides reaction sites for water decomposition.

[0029] Therefore, in order to solve the problems of the need to add sacrificial agents in the process of photocatalytic or photoelectrocatalytic water splitting to produce hydrogen, the easy recombination of photogenerated electrons and holes, and the lack of reactive active sites, the present application creatively proposes to add defect-rich Bi2S3-S V Combined with Co-N4-C, a trapezoidal heterojunction with stable interface structure, high carrier separation efficiency and strong redox activity is constructed, in which the built-in electric field drives the photogenerated electrons from Bi2S3-S V The conduction band migrates to the Co single atom site of NC, and the Co-S coordination with Bi2S3-S V The interface forms a strong coupling, which accelerates the transfer of holes to molecules such as formaldehyde. At the same time, the sulfur vacancies act as electron capture centers to reduce the recombination of photogenerated electrons and holes, promote the adsorption and dissociation of H2O molecules, and provide the required H for the photoelectrocatalytic hydrogen production reaction. + , and use Co single atoms as "electron channels" to further accelerate interfacial charge transfer. Synchrotron radiation results show that Bi2S3-S V The Co K-edge XANES curve of the / Co-N4-C catalyst is between CoPc and Co3O4, proving that the valence state of the Co atom in the catalyst is between +2 and +3. V The valence state of Co in the / Co-N4-C catalyst is about +2.25. The R space transformation of the EXAFS spectrum clearly shows the coordination information of the Co element in the catalyst sample. Compared with Co Foil and Co3O4, Bi2S3-S V No obvious Co-Co peak was observed in the / Co-N4-C sample, which proves that the Co elements are not bonded to each other and the Bi2S3-S V / Co-N4-C sample has obvious Co-N / S coordination bonds, which proves that Bi2S3-S VIn the / Co-N4-C sample, Co exists in the form of a single atom, and a synergistic coordination structure of Co with N and S is formed. In addition, adding formaldehyde or dye to the electrolyte solution instead of the traditional hole sacrificial agent consumes a large number of holes, allowing more electrons to participate in the hydrogen evolution reaction on the platinum electrode, thereby achieving efficient photoelectrocatalytic hydrogen production coupled with formaldehyde oxidation and other reactions. This is an effective strategy to improve catalytic efficiency and reduce the cost of catalytic reactions. The use of non-metallic defects (sulfur / oxygen vacancies) and amorphous substrates to synergistically anchor variable valence single atoms and in-situ growth strategies and solvothermal methods to prepare single-atom synergistically coordinated Bi2S3-S V There is no report on the process of using / Co-N4-C composite catalytic material for photoelectrocatalytic hydrogen production coupled with anodic oxidation of formaldehyde.

[0030] In view of this, the present invention provides a method for preparing a single-atom cooperative coordination composite photoelectrocatalyst, which utilizes non-metallic defects (sulfur / oxygen vacancies) and amorphous substrates to coordinately anchor variable-valence single atoms and in-situ growth strategies and solvothermal methods to achieve Bi2S3-S V The coordination complex of Co-N4-C and Bi2S3-S was generated in situ by liquid phase sulfurization with thioacetamide as the sulfur source. V By adjusting the sulfur source ratio and reducing the concentration of thioacetamide, sulfur defects were directly introduced during the sulfurization process, and then the annealing process was combined to promote the transfer of Co single atoms to Bi2S3-S V Interface migration to form Co-S y The unique sulfur vacancy and Co single atom double coordination synergistic effect was constructed to achieve efficient photoelectrocatalytic hydrogen production coupled with formaldehyde oxidation and other reactions. V / Co-N4-C composite photoelectrocatalyst. Example 1

[0031] A method for preparing a single-atom cooperative coordination composite photoelectric catalyst.

[0032] (1) Add 0.378 g Co(NO3)2·6H2O to 20 mL methanol and stir thoroughly for 10 min. Similarly, add 0.854 g 2-MI to 20 mL methanol and stir thoroughly for 20 min. Quickly drop the 2-MI solution into the Co(NO3)2·6H2O solution and stir vigorously for 10 min. Then, let it stand at room temperature for 20 min to precipitate. Separate the precipitate by centrifugation and wash it with anhydrous ethanol several times. Finally, dry the obtained product in a vacuum drying oven at 80 °C for 12 h and grind it to obtain ZIF-67 crystals.

[0033] (2) 1.0 g ZIF-67 was placed in a N2 atmosphere, heated to 800 °C for 2 h, and then cooled to room temperature to obtain Co-N4-C. Subsequently, 0.97 g Bi(NO3)3·5H2O was dissolved in 20 mL ethanol solution and stirred until completely dissolved. Then, 1.0 g Co-N4-C was added and dispersed therein. After ultrasonic immersion for 60 min, the mixture was dried at 60 °C for 24 h to obtain Co-N4-C@Bi 3+ ;

[0034] (3) Add 1.0 g Co-N4-C@Bi 3+ and 0.15 g TAA were dissolved in 200 mL deionized water / ethylene glycol mixed solution and stirred for 60 min. The stirred solution was then transferred into a solvent thermal reactor and reacted at 200 °C for 12 h. The obtained product was washed with anhydrous ethanol for several times and finally dried in a vacuum drying oven at 80 °C for 12 h to obtain Co-N4-C@Bi2S3-S V .

[0035] (4) 1.0 g Co-N4-C@Bi2S3-S V Place it in an Ar atmosphere, heat it to 350 °C and hold it for 60 min, and then cool it to room temperature to obtain Bi2S3-S V / Co-N4-C composite photoelectrocatalyst. Example 2

[0036] A method for preparing a single-atom cooperative coordination composite photoelectric catalyst.

[0037] (1) Add 0.567 g Co(NO3)2·6H2O to 30 mL methanol and stir thoroughly for 15 min. Similarly, add 1.281 g 2-MI to 30 mL methanol and stir thoroughly for 30 min. Quickly drop the 2-MI solution into the Co(NO3)2·6H2O solution and stir vigorously for 15 min. Then, place it at room temperature to precipitate for 30 min. Separate the precipitate by centrifugation and wash it with anhydrous ethanol several times. Finally, dry the obtained product in a vacuum oven at 60 °C for 18 h and grind it to obtain ZIF-67 crystals.

[0038] (2) 1.5 g ZIF-67 was placed in a N2 atmosphere, heated to 750 °C for 2.5 h, and then cooled to room temperature to obtain Co-N4-C. Subsequently, 1.455 g Bi(NO3)3·5H2O was dissolved in 30 mL ethanol solution and stirred until completely dissolved. Then, 1.5 g Co-N4-C was added and dispersed therein. After ultrasonic impregnation for 90 min, the mixture was dried at 80 °C for 40 h to obtain Co-N4-C@Bi 3+ ;

[0039] (3) Add 1.5 g Co-N4-C@Bi 3+ and 0.225 g TAA were dissolved in 300 mL deionized water / ethylene glycol mixed solution and stirred for 90 min. The stirred solution was then transferred into a solvent thermal reactor and reacted at 180 °C for 14 h. The obtained product was washed with anhydrous ethanol for several times and finally dried in a vacuum drying oven at 60 °C for 18 h to obtain Co-N4-C@Bi2S3-S V .

[0040] (4) 1.5 g Co-N4-C@Bi2S3-S V Place it in an Ar atmosphere, heat it to 450 °C and hold it for 40 min, then cool it to room temperature to obtain Bi2S3-S V / Co-N4-C composite photoelectrocatalyst. Example 3

[0041] A method for preparing a single-atom cooperative coordination composite photoelectric catalyst.

[0042] (1) Add 0.756 g Co(NO3)2·6H2O to 40 mL methanol and stir thoroughly for 20 min. Similarly, add 1.708 g 2-MI to 40 mL methanol and stir thoroughly for 40 min. Quickly drop the 2-MI solution into the Co(NO3)2·6H2O solution and stir vigorously for 20 min. Then, let it stand at room temperature for 40 min to settle. Separate the precipitate by centrifugation and wash it with anhydrous ethanol several times. Finally, dry the obtained product in a vacuum oven at 70 °C for 14 h and grind it to obtain ZIF-67 crystals.

[0043] (2) 2.0 g ZIF-67 was placed in a N2 atmosphere, heated to 700 °C for 3 h, and then cooled to room temperature to obtain Co-N4-C. Subsequently, 1.94 g Bi(NO3)3·5H2O was dissolved in 40 mL ethanol solution and stirred until completely dissolved. Then, 2.0 g Co-N4-C was added and dispersed therein. After ultrasonic impregnation for 120 min, the mixture was dried at 70 °C for 48 h to obtain Co-N4-C@Bi 3 + ;

[0044] (3) Add 2.0 g Co-N4-C@Bi 3+ and 0.30 g TAA were dissolved in 400 mL of deionized water / ethylene glycol mixed solution and stirred for 120 min. The stirred solution was then transferred into a solvent thermal reactor and reacted at 220 °C for 10 h. The obtained product was washed with anhydrous ethanol for several times and finally dried in a vacuum drying oven at 70 °C for 14 h to obtain Co-N4-C@Bi2S3-S V .

[0045] (4) 2.0 g Co-N4-C@Bi2S3-S V Place it in an Ar atmosphere, heat it to 400 °C and hold it for 50 min, and then cool it to room temperature to obtain Bi2S3-S V / Co-N4-C composite photoelectrocatalyst.

[0046] In some embodiments of the present application, according to the above preparation method process, Figure 1 The flowchart of sample preparation in the preparation method provided in the above-mentioned Examples 1 to 3 is shown.

[0047] In some embodiments of the present application, Figure 2 The Bi2S3-S prepared in Examples 1 to 3 above is shown. V Spherical aberration electron microscope images of / Co-N4-C composite material at different scales.

[0048] For example, in Figure 2 In the figure, (a) shows a spherical aberration electron micrograph with a scale of 5 nm, and the red dotted circle represents a single Co atom; (b) shows a spherical aberration electron micrograph with a scale of 2 nm, and the red dotted circle represents a single Co atom, and the yellow arrow points to the sulfur vacancy S V .

[0049] In some embodiments of the present application, Figure 3 The Bi2S3-S prepared in Examples 1 to 3 above are shown. V Synchrotron radiation spectrum of / Co-N4-C composite materials, including Figure 3 The XANES spectrum shown in area (a) and the EXAFS Fourier transform image shown in area (b).

[0050] In the XANES spectrum, the horizontal axis Energy (eV) represents energy, and the unit is electron volt (eV); the vertical axis Intensity (au) represents intensity, and the unit is arbitrary unit (au).

[0051] Specifically, Figure 3 The middle (a) area shows Co foil, Co3O4 (cobalt tetraoxide), CoPc (cobalt phthalocyanine), Bi2S3-S V / XANES spectrum of Co-N4-C.

[0052] In the EXAFS Fourier transform diagram, the horizontal axis R (Å) represents the distance in angstroms (Å); the vertical axis FT (K 2 x(k))|(au) represents the square of the amplitude modulus after Fourier transformation, and the unit is arbitrary unit (au).

[0053] Specifically, Figure 3 The middle (b) area shows Co foil, Co3O4, CoPc, Bi2S3-S V EXAFS Fourier transform diagram of / Co-N4-C. Example 4

[0054] The photoelectrocatalytic performance test was carried out. The electrolyte solution was a mixed solution of 95 mL KOH (1 mol / L) and 5 mL formaldehyde solution (37-40 wt.%), that is, 100 mL of formaldehyde / KOH mixed solution with a concentration of 0.6 mol / L. V / Co-N4-C composite carbon paper (1×1.5 cm 2 ) as the working electrode, Ag / AgCl electrode as the reference electrode, and platinum sheet as the counter electrode. A pre-prepared 100 mL formaldehyde / KOH mixed solution was added to a quartz container, equipped with a three-electrode device and an electrochemical analyzer, and photoelectrocatalytic experiments were carried out under a 300 W visible light source and a bias voltage of -0.4 V vs. RHE. High-performance liquid chromatography was used to determine the formaldehyde oxidation products and their oxidation rates at different times, and a gas chromatograph was used to determine the amount of H2 produced every half an hour.

[0055] As an example, Figure 4 The photoelectrocatalytic performance of the samples prepared in Examples 1 to 3 is shown, including Figure 4The comparison of photoelectrocatalytic hydrogen production rates of the samples shown in area (a) in the presence and absence of formaldehyde, and the photoelectrocatalytic formaldehyde oxidation rate of the samples shown in area (b).

[0056] Figure 4 In the comparison diagram of the photoelectrocatalytic hydrogen production rate of the samples shown in area (a) in the presence or absence of formaldehyde, the horizontal axis represents different samples, namely Bi2S3, Bi2S3-S V , Co-N4-C, Bi2S3 / Co-N4-C, Bi2S3-S V / Co-N4-C; vertical axis H2generation rate (μmol⋅cm −2 ⋅h −1 ) represents the hydrogen generation rate, in μmol⋅cm −2 ⋅h −1 (micromoles per square centimeter per hour). Specifically, the hydrogen production rate increases from left to right, and the hydrogen production rate is faster in the presence of formaldehyde.

[0057] Figure 4 In the sample photoelectrocatalytic formaldehyde oxidation rate diagram shown in area (b), the horizontal axis Time (h) represents time in hours (h); the vertical axis In (C0 / Ct) represents the natural logarithm of the ratio of the initial formaldehyde concentration to the concentration at time t. Specifically, the order of the photoelectrocatalytic formaldehyde oxidation rate from slow to fast is: Bi2S3, Bi2S3-S V , Co-N4-C, Bi2S3 / Co-N4-C, Bi2S3-S V / Co-N4-C, their reaction rate constants k are equal to 0.026, 0.0426, 0.0984, 0.216, and 0.296 respectively.

[0058] In summary, the present invention provides a method for preparing a single-atom cooperative coordination composite photoelectrocatalyst, which adopts non-metallic defects (sulfur / oxygen vacancies) and amorphous substrates to coordinately anchor variable-valence single atoms and in-situ growth strategies and solvothermal methods to prepare Bi2S3-S V / Co-N4-C composite material, the technical method steps are: using Co(NO3)2·6H2O and 2-methylimidazole (hereinafter referred to as 2-MI) as raw materials and methanol solution as solvent to prepare ZIF-67; calcining ZIF-67 at high temperature in N2 atmosphere to obtain a carbon nitrogen material in which Co single atoms are anchored in the form of Co-N4 coordination (hereinafter referred to as Co-N4-C); using Co-N4-C and Bi(NO3)3·5H2O as raw materials and ethanol solution as solvent, ultrasonic impregnation and drying are performed to obtain a surface-loaded Bi 3+ Co-N4-C (hereinafter referred to as Co-N4-C@Bi 3+); with Co-N4-C@Bi 3+ , thioacetamide (hereinafter referred to as TAA) as raw materials, deionized water and ethylene glycol mixed solution as solvent, and Co-N4-C and sulfur vacancy-rich bismuth sulfide (hereinafter referred to as Bi2S3-S V ) composite (hereinafter referred to as Co-N4-C@Bi2S3-S V ); Finally, Co-N4-C@Bi2S3-S V Annealing in Ar atmosphere resulted in a Bi2S3-S V / Co-N4-C composite catalyst. Using carbon paper as substrate, Bi2S3-S V / Co-N4-C photoelectrode. The invention has the advantages of simple preparation process, low production cost, and the prepared Bi2S3-S V The Co-N4-C photoelectrode has a unique dual-coordination structure of Co single atoms, in which the Co-N4 site can stabilize the Co atom and regulate its d-band center, enhancing the adsorption and activation of formaldehyde (HCHO), while the Co-S coordination with Bi2S3-S V The interface forms a strong coupling, accelerating the transfer of holes to molecules such as formaldehyde, while cooperating with sulfur vacancies as electron capture centers to reduce the recombination of photogenerated electrons and holes, promote the adsorption and dissociation of H2O molecules, and promote the photoelectrocatalytic hydrogen evolution reaction (HER). In addition, sulfur vacancies can also optimize the electronic structure of the Bi2S3 surface, reduce the activation energy of oxidation of formaldehyde, and realize Bi2S3-S V / Co-N4-C highly efficient photocatalytic hydrogen production coupled with formaldehyde oxidation and other reactions. V / Co-N4-C also has the advantages of strong visible light response, tight interface bonding, stable structure and rich active sites, and is expected to be used in the fields of photoelectrocatalytic reduction of CO2, degradation of pollutants and production capacity.

[0059] Without limitation to this, any changes or substitutions that are not conceived through creative work should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined in the claims.

Claims

1. A method for preparing a single-atom cooperative coordination composite photoelectrocatalyst, characterized in that: include: (1) Take a certain amount of Co(NO3)2·6H2O and 2-MI and dissolve them in an appropriate amount of methanol solution. After stirring for 5-120 min, let it stand for 1-12 h and collect it by centrifugation to obtain ZIF-67 crystals. (2) placing a certain amount of ZIF-67 crystals obtained in step (1) in a N2 atmosphere, heating to a certain temperature and maintaining it for 1-6 h, and then cooling to room temperature in the furnace to obtain Co-N4-C; (3) Take a certain amount of Bi(NO3)3·5H2O and dissolve it in an appropriate amount of ethanol solution. After stirring until it is completely dissolved, add a certain amount of Co-N4-C and disperse it in it. After ultrasonic immersion for 10-180 min, dry it to obtain Co-N4-C@Bi 3+ ; (4) Take a certain amount of Co-N4-C@Bi 3+ and a certain amount of TAA are dissolved in an appropriate amount of deionized water / ethylene glycol mixed solution and stirred thoroughly for 10-120 min; (5) The solution stirred completely in step (4) was transferred into a solvent thermal reactor and reacted at a certain temperature for 6-24 h. The obtained product was washed and vacuum dried to obtain Co-N4-C@Bi2S3-S V ; (6) A certain amount of Co-N4-C@Bi2S3-S V Place it in an Ar atmosphere, heat it to a certain temperature and keep it for 30-240 min, and then cool it to room temperature to obtain Bi2S3-S V / Co-N4-C composite photoelectrocatalyst.

2. The preparation method according to claim 1, characterized in that: The mass of Co(NO3)2·6H2O used in step (1) is 0.1-10 g, the mass of 2-MI is 0.1-10 g, and the volume of the methanol solution is 10-1000 mL.

3. The preparation method according to claim 1, characterized in that: The mass of ZIF-67 used in the step (2) is 0.1-20 g, and the heating temperature is 600-1000 °C.

4. The preparation method according to claim 1, characterized in that: In the step (3), the mass of Bi(NO3)3·5H2O is 0.1-10 g, the volume of the ethanol solution is 10-1000 mL, the mass of Co-N4-C is 0.1-10 g, the drying temperature is 40-90°C, and the drying time is 6-24 h.

5. The preparation method according to claim 1, characterized in that: The Co-N4-C@Bi 3+ The mass of is 0.1-20 g, the mass of TAA is 0.1-20 g, the volume fraction of the deionized water / ethylene glycol mixed solution is 5-95%, and the volume of the deionized water / ethylene glycol mixed solution is 10-1000 mL.

6. The preparation method according to claim 1, characterized in that: In the step (5), the reaction temperature of the solvent thermal reactor is 120-350°C, the vacuum drying temperature is 40-90°C, and the time is 6-24 h.

7. The preparation method according to claim 1, characterized in that: The Co-N4-C@Bi2S3-S used in step (6) V The mass is 0.1-20 g and the heating temperature is 200-600 ℃.

Citation Information

Patent Citations

  • Preparation method and application of monatomic catalyst with Co-N4-C structure

    CN118634852A

  • Double-sulfur-vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst as well as preparation method and application thereof

    CN119524878A

  • Catalyst for methane synthesis, methane production method, and method for producing catalyst for methane synthesis

    JP2019130523A